COMMUNITY EDUCATION THROUGH TIME: A HISTORICAL OVERVIEW OF IDEAS AND THEIR IMPACT ON CONTEMPORARY EDUCATIONAL PRACTICE - Lidija Črnko (Research in Education and Rehabilitation)
The article explores the historical development of ideas in community education and their influence on contemporary lifelong learning practices. Community education combines formal and informal approaches to foster social cohesion, democratic values, and sustainable development, based on principles of participation, local relevance, and connecting individuals with their environment. The article focuses on the analysis of key community education models, including Danish folk high schools, the American community school movement, British village colleges, and French sociocultural animation. Grundtvig's philosophy of "schools for life" in Denmark emphasizes individual cultural and personal growth in a democratic context, while American community schools, founded during the Great Depression, integrate social justice and local problem-solving. In Britain, village colleges connected education with the everyday life of communities, while French socio-cultural animation links education with cultural empowerment. The article also provides insight into Freire's critical pedagogy and Dolci's maieutic method as examples of emancipatory approaches that promote collective reflection and social transformation through dialogue. The author concludes that community education transcends traditional educational models by encouraging active participation, social justice, and sustainable development. This contribution enhances the understanding of key historical, cultural, and social influences shaping modern concepts of community education and raises questions about future possibilities for their development.